2018
DOI: 10.1038/s41598-018-29254-4
|View full text |Cite
|
Sign up to set email alerts
|

Natural and sexual selection drive multivariate phenotypic divergence along climatic gradients in an invasive fish

Abstract: Invasive species that rapidly spread throughout novel distribution ranges are prime models to investigate climate-driven phenotypic diversification on a contemporary scale. Previous studies on adaptive diversification along latitudinal gradients in fish have mainly considered body size and reported either increased or decreased body size towards higher latitudes (i.e. Bergmann’s rule). Our study is the first to investigate phenotypic divergence in multiple traits, including sexually selected traits (size and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 172 publications
1
35
0
Order By: Relevance
“…Likewise, increased reproductive skew in northern populations could indicate higher levels of female‐mediated sexual selection in these populations (Emlen & Oring, ), which could help females to mitigate the negative consequences of sexual harassment and to refine their mate choice (Hamilton, ; Pitcher et al, ), and produce higher‐quality offspring (Ojanguren et al, ). The idea that female‐mediated sexual selection (e.g., via cryptic female choice; Gasparini & Pilastro, ; Pilastro et al, ) increases towards northern population aligns with the results from another study on Chinese G. affinis , suggesting that male‐mediated forms of sexual selection on certain phenotypic traits increase towards southern populations, where males have a modified armament of their gonopodium tips that may improve sperm transfer during coercive mating (Ouyang et al, ).…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Likewise, increased reproductive skew in northern populations could indicate higher levels of female‐mediated sexual selection in these populations (Emlen & Oring, ), which could help females to mitigate the negative consequences of sexual harassment and to refine their mate choice (Hamilton, ; Pitcher et al, ), and produce higher‐quality offspring (Ojanguren et al, ). The idea that female‐mediated sexual selection (e.g., via cryptic female choice; Gasparini & Pilastro, ; Pilastro et al, ) increases towards northern population aligns with the results from another study on Chinese G. affinis , suggesting that male‐mediated forms of sexual selection on certain phenotypic traits increase towards southern populations, where males have a modified armament of their gonopodium tips that may improve sperm transfer during coercive mating (Ouyang et al, ).…”
Section: Discussionsupporting
confidence: 61%
“…At first sight, this result seems to provide support for direct climate‐effects, for instance, via female solicitation of MP to increase genetic variation and/or quality of their offspring under harsh (northern) conditions (Table ). However, path analysis suggested that climatic effects were mainly indirect, mediated by altered life‐history traits, both latitude‐dependent (Ouyang et al, ; Riesch et al, ) and ‐independent. Both types of analyses, however, received relatively low statistical support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations